INTESTINAL HELMINTHIASIS AND HEALTH EDUCATION: AN EXPERIENCE REPORT - de Oliveira, Bianca Ferreira; de Sousa, Anna Beatriz Lobato; Sevilha, Helena da Silva Araújo; da Silva, Élida Maria; da Silva, Bruno Henrique; dos Santos, Laís Tavares; Batista Filha, Ana Júlia Andrade; Nunes, Poliana Lucena; Martins, José Luís Rodrigues; Pinto, Emerith Mayara Hungria; Costa, Murilo Marques; Gomes, Fabiana Silva (Seven Editora, 2026)
Intestinal helminthiasis is associated with poor sanitation, socioeconomic vulnerability, and continuous environmental exposure, mainly affecting children and adolescents and leading to nutritional changes and impaired growth and development. The objective of this study was to report on the experience of an extension project focused on health education about intestinal helminthiasis, developed in a school environment. This is a report on an extension experience carried out within the scope of the Clinical Parasitology discipline of the Biomedicine course at a university located in the interior of the state of Goiás. The activities were developed by students from the course at a state school in the same municipality, involving high school students. The intervention consisted of educational activities structured through dialogued presentations and interactive activities, addressing the biology of intestinal helminths, forms of transmission, clinical manifestations, and preventive measures. During the development of the actions, active participation by the high school students was observed, with recurring questions about transmission routes and prevention practices, in addition to the identification of limited conceptions related to parasitic diseases. The discussions made it possible to broaden the participants' understanding of the relationship between intestinal helminthiasis, nutritional status, and environmental conditions. It was concluded that extension activities focused on health education about intestinal helminthiasis favor the expansion of knowledge in the school community and strengthen the articulation between teaching and extension.DOI: https://doi.org/10.56238/sevened2026.001-002